The Hijrah: a Re-Evaluation Through Contemporary Histography and Moral Implications - Mustapha Adebayo Bello; Uthman Okanlawon Sidiq (Nur Science Institute, 2025)
Most of the works written by scholars on the Hijrah of the Prophet detailed its significance in establishing the Madinan state, which further led to the efflorescence of Islam from that century up to the present time without examining the moral precepts of modern man. Treating historical events from a purely causative angle often reduces its relevance in addressing modern socioeconomic and political challenges. Besides, a recent chronological assessment of the series of events and persons directly involved in the Hijrah has raised queries on the veracity of the age-long popular perception of the roles played by individuals in the accomplishment of the journey. Identifying these two gaps provides us with the lacuna this work is out to fill. While relying on the rules of historiography, it is essential to determine the reliability of the available Islamic historical sources and scrutinize scriptural provisions that make the Prophet’s life a model for all Muslims. So, migration is not only interrogated as a phenomenon with defining significance to the fortune of Islam but scrutinized to verify the accuracy of the order of events and the roles of individuals on the journey. Its planning and execution are also discussed to unravel the inherent lessons for troubleshooting, strategic planning, security consciousness, spiritual fortification, and peacebuilding as guides in life-changing endeavors. Keywords: hijrah, historiography, life endeavours, moral precepts REFERENCES Abdul-Azim, A.Z. (2000), Ṣaḥiḥ Muslim Arabic-English, Riyadh: Darussalam Abdul Azeez, T. (2024), “Felix of Nola and Q9 Verse 40” in https://ibntaofeeq.com/fe;ix-of-nola-and-q9-verse40/ , March 14, 2024, accessed on 01-01-2025 Adamu, A. (nd) “The Establishment of the Sokoto Caliphate and Its Impact on Society and Economy” in The Sokoto Caliphate History and Legacies, 1804-2004, Volume One. p. 5 Ali, M.A. (2002), The Holy Qur’ān with English Translation and Commentary, USA: Ahmadiyya Anjuman Isha’at Islam Lahore Inc. As-Sallaabee, A.M. (2005), The Noble Life of the Prophet, Riyadh: Darussalam, p. 654 Bello, M.A. (2023), “Re-Examining the Hijrah as a Moral Code for Political Formation of State in Islam” in LASU Journal of History & International Studies, Nigeria: Department of History & International Studies, Faculty of Arts, Lagos State University, 76 Cambridge Dictionary, https://dictionary.cambridge.org/dictionary/English/historiography accessed 01-01-2025 Doi, A.I, (1982), Introduction to the Hadith, Lagos: Islamic Publication Bureau, p. 32 Bert, G. Voices of the Saints, Loyola Press, see https://www.loyolapress.com/catholic-resources/saints/saints-stories-for-all-ages/saint-felix-of-nola/ accessed 01-01-2025 Haykal, M.H. (1976), The Life of Muhammad, India: Millat Center, pp. 90-99 Hitti, P.K. (1985). History of the Arabs, United Kingdom: Macmillan Education Limited, pp. 8-118 Ibn Kathir, (2010), The Life of the Prophet Muhammad Al-Sira al-Nabawiya, Karachi: Darul-Ishat Urdu, pp. 3-100 Khalil, S.A. (2003), Atlas on the Prophet’s Biography, Riyadh: Darussalam, p. 22 Khan, M.M. (nd), Translation of the Meanings of Ṣaḥiḥ Bukhari Arabic-English, Lebanon: Dar-al-Arabia Publishing Printing & Distribution Masudu, H. (2001), History of Islam, India: Alfa Publishers & Distributors Srinagar (J & K) Qutb, S. (nd), In the Shade of the Qur’ān, vol. XVIII, Rahim, A. (1990), Islamic History, Nigeria: Taha Publisher Safiur-Rahman, M. (2011), Ar-Raheequl Makhtum: The Sealed Nectar, Riyadh: Darussalam Sidiq, U.O. (2022), “African-Christian King’s Hospitality to Muslim Envoys: A Catalyst for 21st Century Christian-Muslim Relations in Nigeria” in eds. Paramole K.O. Paramole, Salisu, T.M. & Amuni O.K. Impacting the Nigerian Society Through Humanities and Education, Germany: Lambert Academic Publishing Syed A.A. (1873), A Critical Examination of the Life and Teachings of Muhammed, London: Williams and Norgate _____, (1922), A History of the Evolution and Ideals of Islam with a Life of the Prophet, London: Christophers Berners Street. _____, (2008), The Spirit of Islam; or the Life and Teachings of Mohammed, USA: W.H Allen & Co. Ltd